Gastrointestinal symptoms in patients with postural orthostatic tachycardia syndrome in relation to hemodynamic findings and immunological factors - Tufvesson, Hanna; Hamrefors, Viktor; Fedorowski, Artur; Hansson, Monika; Ohlsson, Bodil (Frontiers in Physiology, 2024)
Gastrointestinal (GI) symptoms are common in postural orthostatic tachycardia syndrome (POTS). We aimed to explore the prevalence and severity of GI symptoms in POTS, and to investigate immunological factors, hemodynamic findings, and their possible association with GI symptoms in POTS. Forty-three patients (93% female, median age 30.6 (26.0–41.0) years), previously diagnosed with POTS and 74 healthy controls (78% female, median age 35.6 (28.8–41.7) years) were included. The participants completed a questionnaire including prevalence of GI symptoms, the irritable bowel syndrome severity scoring system (IBS-SSS), and visual analog scale for IBS (VAS-IBS). All POTS patients were previously examined by tilt test (2010–2021) and the vast majority with more recent active standing test (2017–2021), which included monitoring of heart rate (HR). ΔHR was calculated as difference between supine and upright position. Continuous variables from IBS-SSS and VAS-IBS were correlated to ΔHR. A microarray containing several autoantigens commonly targeted in systemic autoimmune disorders was used to assess prevalent autoantibodies in POTS and controls. Total IgE and S-tryptase were analyzed. GI symptoms were more prevalent and severe in POTS than in controls; nausea being the most prevalent (79.1% vs 4.9%, p < 0.001) and bloating and flatulence being the most severe (median 65 (25–88) vs 0 (0–14), p < 0.001). The median total IBS-SSS was 213 (135–319) in POTS vs 13 (0–54) in controls (p < 0.001). Total IBS-SSS was associated with low psychological wellbeing (r = 0.539, p < 0.001) in POTS. ΔHRmax correlated inversely with abdominal pain (r = −0.406, p = 0.007). After adjustments for psychological wellbeing, total IBS-SSS still associated inversely with ΔHR10min (β: 4.748; 95% CI: −9.172 to −0.324; p = 0.036). Similar results were seen with active standing test. The prevalence of autoantibodies did not differ between POTS and controls (29.4% vs 33.3%, p = 0.803). There was no association between GI symptoms and autoantibody status. Total IgE and tryptase were elevated in a few cases. This study confirms the high prevalence of GI symptoms in POTS. More pronounced tachycardia upon tilt table testing seems to be inversely correlated with severity of chronic GI symptoms in POTS. This study did not support the hypothesis that POTS is associated with immunological factors.